2021
DOI: 10.3390/parasitologia1020007
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Toxoplasmosis: Mechanisms of Retinal Infection and Experimental Models

Abstract: Ocular toxoplasmosis (OT) is caused by the parasite Toxoplasma gondii and affects many individuals throughout the world. Infection may occur through congenital or acquired routes. The parasites enter the blood circulation and reach both the retina and the retinal pigment epithelium, where they may cause cell damage and cell death. Different routes of access are used by T. gondii to reach the retina through the retinal endothelium: by transmission inside leukocytes, as free parasites through a paracellular rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 66 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…[16,17] 2 Lesions caused by the parasite usually heal in two to four months in immunocompetent patients and a study reveals that in about 70 % of cases of patients who seek an ophthalmologist, the lesions resulting from OT that heal are associated with other lesions. [17,18] The study carried out by our research group revealed that OT represents 27 % of eye diseases affecting patients in the northwest region of the state of São Paulo, Brazil. [19] Infection by the parasite is recognized as the most common zoonotic disease in the world, due to its worldwide distribution and the large number of intermediate hosts.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] 2 Lesions caused by the parasite usually heal in two to four months in immunocompetent patients and a study reveals that in about 70 % of cases of patients who seek an ophthalmologist, the lesions resulting from OT that heal are associated with other lesions. [17,18] The study carried out by our research group revealed that OT represents 27 % of eye diseases affecting patients in the northwest region of the state of São Paulo, Brazil. [19] Infection by the parasite is recognized as the most common zoonotic disease in the world, due to its worldwide distribution and the large number of intermediate hosts.…”
Section: Introductionmentioning
confidence: 99%